Transcriptomic Analysis of Differentially Expressed Genes during Flower Organ Development in Genetic Male Sterile and Male Fertile Tagetes erecta by Digital Gene-Expression Profiling. - Ye Ai; Qinghua Zhang; Weining Wang; Chunling Zhang; Zhe Cao; Manzhu Bao; Yanhong He (PLoS ONE)
Tagetes erecta is an important commercial plant of Asteraceae family. The male sterile (MS) and male fertile (MF) two-type lines of T. erecta have been utilized in F1 hybrid production for many years, but no report has been made to identify the genes that specify its male sterility that is caused by homeotic conversion of floral organs. In this study, transcriptome assembly and digital gene expression profiling were performed to generate expression profiles of MS and MF plants. A cDNA library was generated from an equal mixture of RNA isolated from MS and MF flower buds (1 mm and 4 mm in diameter). Totally, 87,473,431 clean tags were obtained and assembled into 128,937 transcripts among which 65,857 unigenes were identified with an average length of 1,188 bp. About 52% of unigenes (34,176) were annotated in Nr, Nt, Pfam, KOG/COG, Swiss-Prot, KO (KEGG Ortholog database) and/or GO. Taking the above transcriptome as reference, 125 differentially expressed genes were detected in both developmental stages of MS and MF flower buds. MADS-box genes were presumed to be highly related to male sterility in T. erecta based on histological and cytological observations. Twelve MADS-box genes showed significantly different expression levels in flower buds 4 mm in diameter, whereas only one gene expressed significantly different in flower buds 1 mm in diameter between MS and MF plants. This is the first transcriptome analysis in T. erecta and will provide a valuable resource for future genomic studies, especially in flower organ development and/or differentiation.